The Maillard reaction in traditional method sparkling wine - Charnock, Hannah M.; Pickering, Gary J.; Kemp, Belinda S. (Frontiers in Microbiology, 2022)
The Maillard reaction between sugars and amino acids, peptides, or proteins generates a myriad of aroma compounds through complex and multi-step reaction pathways. While the Maillard has been primarily studied in the context of thermally processed foods, Maillard-associated products including thiazoles, furans, and pyrazines have been identified in aged sparkling wines, with associated bready, roasted, and caramel aromas. Sparkling wines produced in the bottle-fermented traditional method (Méthode Champenoise) have been the primary focus of studies related to Maillard-associated compounds in sparkling wine, and these wines undergo two sequential fermentations, with the second taking place in the final wine bottle. Due to the low temperature (15 +/- 3 deg C) and low pH (pH 3 – 4) conditions during production and aging, we conclude that Maillard interactions may not proceed past intermediate stages. Physicochemical factors that affect the Maillard reaction are considered in the context of sparkling wine, particularly related to pH-dependent reaction pathways and existing literature pertaining to low temperature and/or low pH Maillard activity. A focus on the origins and composition of precursor species (amino acids and sugars) in sparkling wines is presented, as well as the potential role of metal ions in accelerating the Maillard reaction. Understanding the contributions of individual physicochemical factors to the Maillard reaction in sparkling wine enables a clearer understanding of reaction pathways and sensory outcomes. Advancements in analytical techniques for monitoring the Maillard reaction are also described, and important areas of future research on this topic are identified.